Demonstration of proteolytic activation of the epithelial sodium channel (ENaC) by combining current measurements with detection of cleavage fragments - Krappitz, Matteus; Korbmacher, Christoph; Härteis, Silke (Journal of Visualized Experiments, 2014)
The described methods can be used to investigate the effect of proteases on ion channels, receptors, and other plasma membrane proteins heterologously expressed in Xenopus laevis oocytes. In combination with site-directed mutagenesis, this approach provides a powerful tool to identify functionally relevant cleavage sites. Proteolytic activation is a characteristic feature of the amiloride-sensitive epithelial sodium channel (ENaC). The final activating step involves cleavage of the channel's ?-subunit in a critical region potentially targeted by several proteases including chymotrypsin and plasmin. To determine the stimulatory effect of these serine proteases on ENaC, the amiloride-sensitive whole-cell current (?Iami) was measured twice in the same oocyte before and after exposure to the protease using the two-electrode voltage-clamp technique. In parallel to the electrophysiological experiments, a biotinylation approach was used to monitor the appearance of ?ENaC cleavage fragments at the cell surface. Using the methods described, it was demonstrated that the time course of proteolytic activation of ENaC-mediated whole-cell currents correlates with the appearance of a ?ENaC cleavage product at the cell surface. These results suggest a causal link between channel cleavage and channel activation. Moreover, they confirm the concept that a cleavage event in ?ENaC is required as a final step in proteolytic channel activation. The methods described here may well be applicable to address similar questions for other types of ion channels or membrane proteins.
EVALuna2:4494